2014
DOI: 10.1590/s1807-25772014000100001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the addition of chlorhexidine diacetate on bond strength of a high-viscosity glass ionomer cement to sound and artificial caries-affected dentin

Abstract: INTRODUCTION: The aim of adding chlorhexidine (CHX) to glass ionomer cements (GIC) is to improve their antibacterial property, but it may interfere with their bond to dentin. OBJECTIVE: To evaluate the influence of adding chlorhexidine diacetate at different concentrations to a high-viscosity GIC on its bond to sound and artificial caries-affected dentin. MATERIAL AND METHOD: Eighty human third molars were used, on which an area of dentin was exposed on the occlusal surface. Half of the specimens were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Contemporary dentistry advocates a minimally invasive approach to cavity preparations removing infected dentin while preserving caries-affected dentin that is amenable to reorganization [15] this study used affected dentin as a substrate for bond strength testing, a design consistent with previous work by Nakajima et al [24], Yoshiyama et al [2]. Arrais et al [25], Erhardt et al [5], De Carvalho et al [26], Carvalhoet al [27], Scheffel et al [3], Becci et al [15], Lenzi et al [4], Mattos et al [28], and Li et al [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Contemporary dentistry advocates a minimally invasive approach to cavity preparations removing infected dentin while preserving caries-affected dentin that is amenable to reorganization [15] this study used affected dentin as a substrate for bond strength testing, a design consistent with previous work by Nakajima et al [24], Yoshiyama et al [2]. Arrais et al [25], Erhardt et al [5], De Carvalho et al [26], Carvalhoet al [27], Scheffel et al [3], Becci et al [15], Lenzi et al [4], Mattos et al [28], and Li et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the microbiological method was used to induce dentinal [14] and Sattabanasuk et al [20] reported the need for standardization of the method used to remove carious lesions in studies seeking to evaluate the bond strength of adhesive systems. In the present study, infected dentin was removed while affected dentin was preserved by using the standard method described by Arrais et al [25], Becci et al [15], and Scheffel et al [3]. Infected dentin was worn down with 320-grit15 silicon carbide sandpaper until resistance to manual pressure with a dental explorer was encountered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study Becci et al 25 (2014) compared the bond strength of a GIC with different concentrations of CHX to sound and caries-affected dentin only in the period of 24 hours. Although in both the cited study and the present study, the infected dentin was manually removed using 320-grit silicon carbide abrasive, the authors showed that the condition of the substrate had no influence on the immediate bond strength values.…”
Section: Discussionmentioning
confidence: 99%